Faktor-Faktor Yang Memepengaruhi Disiplin Kerja Pegawai Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Purbalingga - Eka Nur Fadzilah; Arinastuti Arinastuti; Ratna Puji Astuti (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
Abstract This research is based on gap research in the form of differences in research results for each variable. This research aims to determine the influence of leadership, work environment, organizational culture, and punishment partially and simultaneously on work discipline at the Purbalingga Regency Population and Civil Registration Service. Determination of the sample using Proportionate Stratified Random Sampling. Data obtained through distributing questionnaires to research respondents totaling 67 people. The analysis used is multiple linear regression with least squares equations and hypothesis testing using t-count to test partial regression coefficients and F-count to test the effect simultaneously with a confidence level of 5%. The results of the research show that leadership and work environment punishment have a positive and significant effect on work discipline. Meanwhile, organizational culture has a negative and significant effect on work discipline. From the research results, it can be implied that the leadership of the Population and Civil Registration Service provides motivation to employees, provides a decent workplace, pays more attention to employees, and improves work discipline.